From gender bias to gender awareness in medical education - Verdonk, Petra; Benschop, Yvonne W. M.; de Haes, Hanneke C. J. M.; Lagro-Janssen, Toine L. M. (Advances in Health Sciences Education, 2009)
Gender is an essential determinant of health and illness. Gender awareness in doctors contributes to equity and equality in health and aims towards better health for men and women. Nevertheless, gender has largely been ignored in medicine. First, it is stated that medicine was ‘gender blind’ by not considering gender whenever relevant. Secondly, medicine is said to be ‘male biased’ because the largest body of knowledge on health and illness is about men and their health. Thirdly, gender role ideology negatively influences treatment and health outcomes. Finally, gender inequality has been overlooked as a determinant of health and illness. The uptake of gender issues in medical education brings about specific challenges for several reasons. For instance, the political-ideological connotations of gender issues create resistance especially in traditionalists in medical schools. Secondly, it is necessary to clarify which gender issues must be integrated in which domains. Also, some are interdisciplinary issues and as such more difficult to integrate. Finally, schools need assistance with implementation. The integration of psychosocial issues along with biomedical ones in clinical cases, the dissemination of literature and education material, staff education, and efforts towards structural embedding of gender in curricula are determining factors for successful implementation. Gender equity is not a spontaneous process. Medical education provides specific opportunities that may contribute to transformation for medical schools educate future doctors for future patients in future settings. Consequently, future benefits legitimize the integration of gender as a qualitative investment in medical education.
Keywords: approches et analyses; discipline; europe; formation des médecins; médecine; pays-bas; projet charge mentale; rapports sociaux de sexe; régions géographiques; santé; sciences; sexisme; stéréotypes de genre; systèmes d'oppressions; thématiques; éducation

L’économie politique du sexe : transactions sur les femmes et systèmes de sexe/genre - Rubin, Gayle (Les cahiers du CEDREF. Centre d’enseignement, d’études et de recherches pour les études féministes, 1998)
La littérature sur les femmes — tant féministe qu’antiféministe — est une longue rumination quant à la nature et à la genèse de leur oppression et de leur subordination sociale. La question n’est pas sans importance, car les réponses qui lui sont données déterminent la manière dont nous envisageons l’avenir et si nous jugeons réaliste ou non d’espérer une société égalitaire entre les sexes. Plus important, l’analyse des causes de l’oppression des femmes fonde toute estimation de ce qu’il faudrait exactement changer pour réaliser une société sans hiérarchie de genre
Première publication: 1975 http://journals.openedition.org/cedref/171
Keywords: 1900-1999; 1960-1969; 1970-1979; anthropologie; approches et analyses; capitalisme; classe ouvrière; cours; discipline; europe; famille; fem1000; france; féminisme matérialiste; histoire et politique; inégalités; marxisme; patriarcat; premier cycle; psychanalyse; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences; sciences humaines; soc1016; soc2014; sociologie; systèmes d'oppressions; thématiques; théories féministes